2004
DOI: 10.1089/152308604771978372
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration of Thioredoxin Decreases Brain Damage Following Transient Focal Cerebral Ischemia in Mice

Abstract: Thioredoxin (TRX) is induced by a variety of oxidative stimuli and shows cytoprotective roles against oxidative stress. To clarify the possibility of clinical application, we examined the effects of intravenously administered TRX in a model of transient focal cerebral ischemia in this study. Mature male C57BL/6j mice received either continuous intravenous infusion of recombinant human TRX (rhTRX) over a range of 1-10 mg/kg, bovine serum albumin, or vehicle alone for 2 h after 90-min transient middle cerebral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 42 publications
5
75
0
1
Order By: Relevance
“…Immunostaining was apparent in both cytosolic and mitochondrial compartments and showed marked variation in intensity between individual cells. These results confirm and extend data from a recent report by using Western blot analysis demonstrating that systemically administered hTrx can enter ischemic͞reperfused brain tissue (20).…”
Section: Administration Of Htrx Before Reperfusion Reduces Mi͞r Myocasupporting
confidence: 91%
“…Immunostaining was apparent in both cytosolic and mitochondrial compartments and showed marked variation in intensity between individual cells. These results confirm and extend data from a recent report by using Western blot analysis demonstrating that systemically administered hTrx can enter ischemic͞reperfused brain tissue (20).…”
Section: Administration Of Htrx Before Reperfusion Reduces Mi͞r Myocasupporting
confidence: 91%
“…This study shows that TCP-1 levels are increased in ischemic brain injury, representing a compensatory cellular mechanism to recover cytoskeletal damage. Thioredoxin, a redox protein, inhibits apoptosis and protects against oxidative stress [10,26]. Thioredoxin overexpression decreases brain damage against focal cerebral ischemia and protects against oxidative stress [10,26].…”
Section: Discussionmentioning
confidence: 99%
“…Thioredoxin, a redox protein, inhibits apoptosis and protects against oxidative stress [10,26]. Thioredoxin overexpression decreases brain damage against focal cerebral ischemia and protects against oxidative stress [10,26]. Peroxiredoxin-2 has thioredoxin-dependent peroxidase activity utilizing thioredoxin and thioredoxin reductase as electron donors for anti-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The same mice were also more resistant to hippocampal damage produced by administration of the excitotoxin kainic acid (401). In mice, intravenous infusion of recombinant human Trx for 2 h after 90 min of MCAO reduced infarct volume, neurological deficit, and protein carbonyl content (i.e., a marker of protein oxidation) (153). Overexpression of Trx in PC12 cells prolonged their survival in culture medium lacking nerve growth factor (NGF) and serum, suggesting that Trx can delay neuronal apoptosis (170); subsequent studies showed that Trx was a direct inhibitor of the apoptosis signal-regulating kinase (ASK) 1 (352).…”
Section: Sod2mentioning
confidence: 97%